Turkey : Reforming the Health Sector for Improved Access and Efficiency, Volume 2. Background Papers - World Bank (Washington, DC, 2013)
Fundamental and systemic changes would have to be brought about in the ways that health care is financed, delivered, organized, and managed in Turkey in order to meet the ultimate objective of improving the health status of people, and not only meet but surpass the health-related Millennium Development Goals. This would require significant improvements in resource mobilization, allocation and utilization, enhanced efficiency in production and delivery of health services, including primary and hospital care, and greater emphasis on clinical quality and patient access to health services. Against this backdrop, the World Bank and the Government of Turkey agreed to undertake an intensive review of all aspects of the health sector, and the present report is produced from this effort. One objective of an evaluation at this juncture is to lay the foundation for developing a medium-term health sector strategy and a prioritized action plan aimed at improving access to health services, enhancing equity in utilization, increasing cost-effectiveness, enhancing quality of care and improving health outcomes overall. In particular, the emphasis of this study is to develop viable medium-term options for enhancing the health services coverage of poor and vulnerable groups and examine which priorities and approaches are likely to be most pro-poor. The study also examines the appropriate role of the government in providing health services, and the institutional, managerial, and administrative requirements for developing an efficient, sustainable, and patient-responsive health system. In doing so, the study examines ways in which public spending can be oriented so as to maximize its effects on access, equity, and efficiency in the health sector. An added objective of this study is to engage policy makers and major stakeholders in discussions and debates on health reforms and bring about a consensus among them not only on broad principles but also in terms of integrated and coordinated approach to implementing reform measures. This report is organized in two volumes. Volume 1 contains a discussion of health sector priorities and key recommendations for developing a medium-term reform strategy for Turkey's health sector. Volume 1 concludes with an implementation plan for the short and medium terms. Volume 2 contains the full background reports and data annexes that form the basis of the suggested health system reform.